Marcos técnicos e legais de gerenciamento de PCB no setor elétrico: uma revisão crítica e propostas para o Brasil - Mariana Garcia Costa (2016)
Brazil has ratified the Stockholm Convention on Persistent Organic Pollutants, which includes Polychlorinated Biphenyls (PCB) among others. PCB were used mainly as insulating dielectric fluid in electrical equipment, heat transfer and hydraulic fluids. This work aims to present the main PCB management aspects adopted by eletric sector in the six countries that most consumed PCB and European Union and to propose adequate strategies to the Brazilian reality to fullfil the Stockholm Convention Protocol. An extensive literature review was carried out, followed by critical assessment, historic and current analysis of Brazilian management status, resulting into technical and legal proposals. The main tests available for determining the presence of PCB in oil are: density test; PCB screening kits throught colorimetric reaction or chlorine ion electrode; gas chromatography analysis. The different PCB waste types, their concentration and composition of the electrical equipment with distinct decontamination difficulties depending on the material, make the disposal choice a complex process. Considering Brazilian national economic reality, as well its historically low environmental risk and theexistence of legal and regulatory framework since the 80s, it is proposed that Brazil adopts management policies similar to the Stockholm Convention and which is adopted in many developed countries, mainly related to the disposal deadlines, threshold concentrations of materials, PCB analysis and final disposal methods. It is also suggested that a national statistical inventory with defined criteria is carried out, enabling prioritization of high-risk groups of equipments. It is indeed important to eliminate PCB in Brazil for environmental protection, but one should evaluate how to accomplish this, ensuring balance among the three mainsustainability aspects (environmental, social and economical) to ensure the creation of a regulation that perceives national reality without unnecessarily harming the consumer.